The Effect of Customer Value and Brand Trust on Customer Loyalty of Tabot Savings Bank Bengkulu Main Branch - Fery Gustian; Ahmad Soleh; Mimi Kurnia Nengsih (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study is to determine the effect of customer value and brand trust on customer loyalty Tabot Savings at Bank Bengkulu Main Branch. This research is a quantitative descriptive study with data collection methods through questionnaires. The sample in this study is were 82 customers of Tabot Savings at Bank Bengkulu Main Branch. The sampling method was purposive sampling. The data analysis method used includes validity test, reliability test, multiple linear regression analysis and hypothesis testing.The results of this study indicate that customer value and brand trust partially have a positive and significant effect on customer loyalty of Tabot Savings at Bank Bengkulu Main Branch. And simultaneously customer value and brand trust have a significant effect on customer loyalty of Tabot Savings at Bank Bengkulu Main Branch.